2020
DOI: 10.3390/microorganisms8081189
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriomic Profiling of Branchial Lesions Induced by Neoparamoeba perurans Challenge Reveals Commensal Dysbiosis and an Association with Tenacibaculum dicentrarchi in AGD-Affected Atlantic Salmon (Salmo salar L.)

Abstract: Amoebic gill disease is a parasitic condition that commonly affects marine farmed Atlantic salmon. The causative agent, Neoparamoeba perurans, induces a marked proliferation of the gill mucosa and focal superficial necrosis upon branchial lesions. The effect that amoebic branchialitis has upon gill associated commensal bacteria is unknown. A 16S rRNA sequencing approach was employed to profile changes in bacterial community composition, within amoebic gill disease (AGD)-affected and non-affected gill tissue. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 76 publications
(82 reference statements)
2
29
0
Order By: Relevance
“…It has been proposed that Tenacibaculum sp. may make up a portion of the mucosal microbiome of Atlantic salmon in seawater [ 46 ], where the presence before and after an outbreak supports that the bacteria should be considered opportunistic pathogens [ 47 , 48 ], potentially inducing tenacibaculosis through dysbiosis [ 49 , 50 , 51 ]. Of the environmental samples, OO had the most T. dicentrarchi , supporting the notion that other organisms associated with netpens can concentrate the bacteria relative to the environment [ 52 , 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that Tenacibaculum sp. may make up a portion of the mucosal microbiome of Atlantic salmon in seawater [ 46 ], where the presence before and after an outbreak supports that the bacteria should be considered opportunistic pathogens [ 47 , 48 ], potentially inducing tenacibaculosis through dysbiosis [ 49 , 50 , 51 ]. Of the environmental samples, OO had the most T. dicentrarchi , supporting the notion that other organisms associated with netpens can concentrate the bacteria relative to the environment [ 52 , 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…2020) indicated that the Tenadi assay also detected several other Tenacibaculum species. Other PCR and qPCR assays to distinguish T. dicentrarchi are available (Slinger et al., 2020; Wilson et al., 2019); like the DICEN and FIN assays, they have not been validated in other studies.…”
Section: Primer or Probe Name Sequence (5ʹ−3ʹ) Melting Temperature (°mentioning
confidence: 99%
“…A new T. dicentrarchi PCR-specific assay was developed for multiplex-PCR due to the Tenadi assay amplicon being of a similar size to other species-specific PCR assays [ 76 ]; however, validation in other studies is needed. A 16S rDNA qPCR assay has been developed to identify T. dicentrarchi and was reported to be specific but needs to be validated and investigated for potential false positives [ 79 ]. MLSA demonstrated that T. dicentrarchi is in Clade two and was the phylogenetic sister to T. ovolyticum and T. soleae [ 35 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…All the fish were reported to have extensive scale loss, small hemorrhagic lesions, ascites, and dark livers [ 120 ]. Recently, exposure trials of Atlantic salmon to Neoparamoeba perurans (causative agent of amoebic gill disorder) identified a weak positive correlation between the presence of N. perurans and T. dicentrarchi in diseased fish [ 79 ]. In some lesions of diseased fish, 70.7% of the mean bacterial abundance was T. dicentrarchi , and there was reduced species richness and diversity indexes in diseased fish compared to naïve fish, supporting that dysbiosis may have implications for tenacibaculosis [ 79 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation